Couples' Time-Use and Aggregate Labor Market Outcomes - Almut Balleer; Monika Merz; Tamás K. Papp (Institute of Labor Economics (IZA), 2021)
We present a model of the time-allocation decision of spouses in order to study the role of heterogeneity in preferences and wages for couples' labor supply. Spouses differ in their tastes for market consumption and non-market goods and activities, and also in their offered or earned wages. They interact in their choices of market hours, homework, and leisure. We estimate the model for married or cohabiting couples in the 2001/02 wave of the German Time-Use Survey using Bayesian techniques. We generate gender-specific own- and cross-wage elasticities of market hours in the cross-section. Elasticities are significantly larger if the wage shock is asymmetric across partners, not symmetric. Aggregating preferences and wages by gender and comparing outcomes for a representative couple with those from heterogenous couples yields a discrepancy between alternative aggregate wage-elasticities. Its size varies with the type of wage shock and the distribution of spouses across the preference-wage space.
Keywords: D12; D13; J22; 330; time-use; spouses' labor supply; aggregation; Bayesian estimation